Pilot evaluation of a fracture process zone in a modified compact tension specimen by X-ray tomography (Fracture and Structural Integrity, 2017)
In the case of quasi-brittle material, there is a zone of non-linear behaving material, near the crack tip. A major part of this zone forms a socalled fracture process zone (FPZ), where mechanisms of material toughening take place. The main idea is to estimate the size of the fracture process zone under various types of load by using X-ray tomography. The estimation of the zone is supported by the theory of linear elastic fracture mechanics (LEFM) that could be a limit case of quasi-brittle mechanics. The size of the zone envelop is provided in X-ray snaps and compared with the theoretical size from LEFM.
Keywords: Fracture process zone; X-ray; Concrete; Composites; Compact tension specimen; Stress intensity factor